PERLAWANAN PEDAGANG PASCA REVITALISASI STUDI PENELITIAN DI PASAR IR. SOEKARNO, KABUPATEN SUKOHARJO - Anugraheni Titis Aprilianawati; Nunik Retno Herawati; warsito -; wachid abdulrahman (Journal of Politic and Government Studies, 2018)
This research concerns about the merchants’ resistance that happened after the revitalization of Pasar Ir. Soekarno-Sukoharjo which is located at Jalan Jenderal Sudirman no. 53 Sukoharjo Regency. This study becomes the first study of this locus because most of the research on this locus only examines the aspects of revitalization implementation. Resistance aspect becomes an interesting thing to be studied in this research because in revitalization, it tends to prioritize the aspect of the market’s physical improvement. Meanwhile, on the other hand revitalization done gives less attention to social aspects so that a resistance from the traders emerges. Thus, this study is intended to examine further the case related to Merchants’ Resistance During Post Revitalization of Ir. Soekarno Market in Sukoharjo Regency This study is based on the key questions that emphasize its substance of the policy-making actors and actors who reject the research locus. Specifically, to keep this research in the theoretical corridor, the authors conduct the research by referring to the question "How is the merchants’ resistance during the post revitalization of Ir. Soekarno market, what causes it to happen, and how is the resolution done?". In order to answer the questions, the researcher uses qualitative descriptive analytic research method using observation data, in-depth interview, documentation study, visual data, and online data. Qualitative research is chosen because this research method does not emphasize generalization but more focused on one case, so that the researcher can capture the phenomenon as a whole proper to the real condition.Based on the result of the research, it is found that in the context of post-revitalization in Ir. Soekarno market there are merchants’ resistance really found in the form of refusing to occupy the kiosks and los that have been provided. According to the facts in the field, that the main cause of the merchants’ resistance occured is because of the demands of economic needs. The resolution against the merchant resistance that has been done has not been successful because in reality, there are still many kiosks and los being emptied. The resolution undertaken is considered to be less paying attention to the advice of the merchanst as the main actor of the resolution.Keywords: Resistance, Merchant, Post Market Revitalization